La ‘questione’ dei cinematografi: tra adeguamenti funzionali ed esigenze di compatibilità / The cinemas ‘question’: between functional adjustments and compatibility requirements - Turco, Maria Grazia; Fasanella, Alessandro (Restauro Archeologico, 2025)
Cinemas represent a unique and inimitable heritage that is often left abandoned or subjected to continuous, incompatible changes in use, mostly driven by economic and speculative needs that risk erasing these architectural testimonies. This is a situation in which architectural heritage is suffering from relentless disputes; these are spaces that are being sold off, demolished and, in the best-case scenario, altered, as they are now considered to be mere consumer products linked to the needs of a market in constant evolution and experimentation. These issues fall squarely within the discipline of Modern Restoration: first and foremost, the issue of ‘compatibility’ of use between new destinations and the specific functions of the building, which often cannot ‘tolerate’ the functional, plant and structural modifications required for new activities. This contribution aims to provide an opportunity to open a discussion on a highly topical issue today, at the center of a broad debate involving history, criticism, cultural theory, and restoration.